EXTRACORPOREAL MEMBRANE OXYGENATION IN INTENSIVE CARE - Роман Александрович Корнелюк; Дмитрий Леонидович Шукевич (Медицина в Кузбассе)
Extracorporeal membrane oxygenation (ECMO) is a modality for providing extracorporeal life support focused at the recovery of gas exchange function and cardiac function. Over the last decades, ECMO has been used as a technique for cardiorespiratory support for heart and lung disease, where conventional treatment is ineffective, particularly in cardiac surgery units. ECMO technology seems to be promising mean during the epidemic peak of H1N1 and other viral and bacterial pathogens associated with lung lesions causing acute respiratory distress syndrome. Thus, ECMO should be considered as a support device, providing temporary life support for potentially reversible cardiac and/or respiratory failure until their recovery or for transplantation candidates. The current review describes the history of ECMO, various indications to ECMO in critically ill patients, its efficiency and complications.